PENENTUAN KADAR ION Pb 2+ (TIMBAL) DALAM RAMBUT KARYAWAN BENGKEL DI KOTA SAMARINDA - Linda Ajang; Bohari Yusuf; Aman S Panggabean (JURNAL KIMIA MULAWARMAN, 2015)
Research on the determination of Pb 2+ ions (lead)in hair repair shop employee in the city of Samarinda. This study aims to determine whether there is a relationship between the concentration of lead ions in the workshop employees hair against old age and work. Measurements of Pb 2+ ions (lead) was performed using Atomic Absorption Spectrophotometer (AAS). Hair cut into small pieces, washed, crushed or burned into ashes and homogenized and analyzed by Atomic Absorption Spectrophotometer (AAS). The results obtained from the measurement and analysis of Pb 2+ ions concentration in hair repair shop employee is 0.2193 ppm and 0.3665 ppm lowest to highest. At the workshop employees there is a relationship between age and levels of Pb 2+ ions (lead) in the hair, while there was no correlation between long working white Pb, it’s based on a statistical analysis of the results of the determination coefficient and linear regression.